GANGLIOSIDES IN DNA VIRUS-TRANSFORMED AND SPONTANEOUSLY TRANSFORMED TUMORIGENIC MOUSE CELL LINES - Mora, Peter T. (1969)
In mouse cell lines transformed by SV40 virus, a decrease was observed in the higher ganglioside homologues disialo-ceramidetetrahexoside and monosialo-ceramidetetrahexoside. Such change was observed only in cells which carry the virus genome, and it correlated with increased saturation density in tissue culture and with rejection in immunologically competent syngeneic host. This indicates that the change is one of the virus-regulated functions, and it is postulated that it relates to the rejection of the virus-transformed cells.